The effectiveness of child focused non-governmental organizations in promoting the rights of children: a case of Murerezi ward. - Sibanda, Lydia (Midlands State University, 2017)
In Zimbabwe, children are the primary victims of poverty, which is the main cause of violation of their fundamental rights. It is important to note that poverty remains the principal cause of the violation of children’s rights because lack of funds seriously impedes access to their basic human needs, which are access to health care, water, food, and education. Despite the existence of child focused NGOs; children’s rights are still being violated. This realisation has resultantly prompted the need for a study focusing on the effectiveness of child focused NGOs in promoting the rights of children riveting to the particular case of Murerezi Ward in Mberengwa District. A study was vital to find out whether child focused NGOs have effectively promoted the rights of children in the area under study and sought to determine whether child focused NGOs approach to child rights promotion is comprehensive and produced intended results. A mixed approach was used in this study. To acquire relevant data the interviews, questionnaires, observation, and focus group discussions was used in Murerezi ward. This helped the researcher to extract relevant information from community members, local leaders, children and child focused NGO staff members. On the ground the community members have witnessed child focused NGOs promoting children’s rights through building of schools, ECD centres, clinic, provision of stationery ,textbooks, access to safe drinking water, bicycles and child protection. However, there are still cases of child labour and child marriages. The study revealed the challenges faced by child focused NGOs and shed light on the prospects for effective child rights promotion in Murerezi ward.